Childhood Influenza Vaccination Is Not a Priority for Parents: A National, Cross-Sectional Survey of Barriers to Childhood Influenza Vaccination in Australia - Maryke S. Steffens; Jessica Kaufman; Katarzyna T. Bolsewicz; Suzanna Vidmar; Maria Christou-Ergos; Majdi M. Sabahelzain; Julie Leask; Justin Boxall; Frank Beard; Margie Danchin (Vaccines)
Background/objectives: Influenza vaccines are recommended and free in Australia for children aged <5 years, but uptake remains low at 25.8% compared to the targets of 40% and 50%. National data on barriers hindering paediatric influenza vaccination can inform strategies to improve uptake. The aim of this study was to measure barriers to influenza vaccination in Australian children aged <5 years. Methods: A national, cross-sectional survey of parents of children aged <5 years was conducted in March/April 2024. Parents were recruited using an online panel and asked about their intention to get an influenza vaccine for their youngest child in the upcoming influenza season. An adapted version of the validated Vaccine Barriers Assessment Tool measured 14 influenza vaccination barriers. Analysis assessed the prevalence of barriers and differences between parents intending to and those unsure or not intending to vaccinate by calculating the prevalence difference and 95% confidence interval. Results: A total of 2000 parents were recruited nationally. The most common barrier was parents feeling distressed when thinking about vaccinating their child against influenza (66.1% of intending parents, 65.6% of unsure/not intending parents). The barrier with the largest difference between intending and not intending/unsure parents was not prioritising their child’s influenza vaccination (47.2% vs. 6.1%, PD = 41.1 ppts, 95% CI: 35.9%, 46.3%). Other barriers with large differences were parents not feeling guilty if their unvaccinated child got influenza (41.5% vs. 7.5%, PD = 34.0 ppts, 95% CI: 28.8%, 39.1%) and parents not believing that influenza vaccines are effective (31.3% vs. 3.0%, PD = 28.2 ppts, 95% CI: 23.6%, 32.9%). Conclusions: Parents should be encouraged and supported to prioritise influenza vaccination alongside routine childhood vaccines in campaigns that emphasise disease risk and the importance, safety and effectiveness of influenza vaccination, and by optimising access to influenza vaccination. We recommend conducting similar surveys regularly to monitor trends in parental barriers to childhood influenza vaccination.